2011
DOI: 10.1186/1471-2407-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GPR39 contributes to malignant development of human esophageal squamous cell carcinoma

Abstract: BackgroundBy using cDNA microarray analysis, we identified a G protein-coupled receptor, GPR39, that is significantly up-regulated in ESCC. The aim of this study is to investigate the role of GPR39 in human esophageal cancer development, and to examine the prevalence and clinical significance of GPR39 overexpression in ESCC.MethodsThe mRNA expression level of GPR39 was analyzed in 9 ESCC cell lines and 50 primary ESCC tumors using semi-quantitative RT-PCR. Immunohistochemistry was used to assess GPR39 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…In recent years, great progress has been made in studies on the pathogenesis of esophageal cancer at the molecular level. It has been confirmed that the genes related to esophageal cancer include P53, cyclin D1, VEGF, GPR39, Wnt-1 and cyclin E (13)(14)(15)(16)(17)(18). Cyclin E, a type of G1 cyclin, was first discovered by Koff et al in 1991 (19).…”
Section: R E T R a C T E D Discussionmentioning
confidence: 98%
“…In recent years, great progress has been made in studies on the pathogenesis of esophageal cancer at the molecular level. It has been confirmed that the genes related to esophageal cancer include P53, cyclin D1, VEGF, GPR39, Wnt-1 and cyclin E (13)(14)(15)(16)(17)(18). Cyclin E, a type of G1 cyclin, was first discovered by Koff et al in 1991 (19).…”
Section: R E T R a C T E D Discussionmentioning
confidence: 98%
“…For example, ZnR/GPR39 silencing in an esophageal squamous cell carcinoma (ESCC) cell line decreased cell proliferation and delayed the cells in the G1/S phase. 52 In addition, ZnR/GPR39 overexpression was detected in specimens of human ESCC and associated to the malignant development of this carcinoma, 52 but the role of Zn 2+ as the ligand of ZnR/GPR39 that promotes these tumorigenic processes remained elusive. Our results, however, do not support an oncogenic effect for ZnR/GPR39, as elevated levels of ZnR/GPR39 were found in differentiating Caco-2 cells compared with cells in the proliferative phase.…”
Section: Discussionmentioning
confidence: 99%
“…A score of 0 was considered negative; 2-3 was considered weak; 4-5 was considered moderate; and 6-7 was considered strong. For statisticalanalysis, 0-3 were counted as low expression, while 4-7 were counted as overexpression [14]. In half of the samples, staining was repeated twice to avoid technical errors, but similar results were obtained in these samples.…”
Section: Immunohistochemistrymentioning
confidence: 99%